The CKD Outcomes and Practice Patterns Study (CKDopps): Rationale and Methods - Mariani, Laura; Stengel, Bénédicte; Combe, Christian; Massy, Ziad A.; Reichel, Helmut; Fliser, Danilo; Pecoits-Filho, Roberto; Lopes, Antonio A.; Yamagata, Kunihiro; Wada, Takashi; Wong, Michelle M.Y.; Speyer, Elodie; et al. (American journal of kidney diseases, 2016)
Minimizing clinical complications in patients with advanced chronic kidney disease (CKD) and improving the transition to dialysis therapy and transplantation represents a challenge, requiring reliable evidence regarding the effects of CKD care on outcomes. The CKD Outcomes and Practice Patterns Study (CKDopps) is a new international prospective cohort study designed to describe and evaluate variation in nephrologist-led CKD practices. CKDopps is underway in Brazil, France, Germany, Japan, and the United States. Diverse national samples of nephrology clinics are being recruited based on random selection stratified by geographic region and clinic characteristics. CKDopps aims to enroll 12,200 non−dialysis-dependent patients with CKD (75% and 25% with estimated glomerular filtration rates < 30 and 30-<60mL/min/1.73m2, respectively) to be followed up for 3 to 5 years. Demographic, comorbid condition, laboratory, and treatment-related variables are collected at 6-month intervals; patient-reported data are collected annually and more frequently near the transition to end-stage kidney disease; nephrologist practice surveys are collected annually. Outcomes include mortality, end-stage kidney disease, other clinical events (eg, acute kidney injury, hospitalizations, infections, cardiovascular events, and transplant wait-listing), and patient-reported outcomes. For the targeted sample size of 12,200 patients and 160 clinics, CKDopps has 80% power to detect HRs of 1.31 for mortality and 1.19 for mortality or transition to end-stage kidney disease. CKDopps does not capture care provided in settings outside nephrology clinics (eg, primary care) or patients with CKD not receiving medical care. CKDopps is designed to characterize nephrology clinic practice variation and identify practices associated with better outcomes, with particular focus on advanced CKD, transition to end-stage kidney disease, and the patient experience. Because data will be collected during routine clinical care in real-world practice, analyses may yield practical readily implementable findings. CKDopps aims to establish a multinational infrastructure for research, collaboration, and ancillary investigation. Additional countries are encouraged to join.